Analysis of Hindering Factors Among Islamic Education Teachers of Smart School in The Use of Teaching Aids/ Analisa Faktor Halangan Guru Pendidikan Islam Sekolah Bestari Dalam Penggunaan Bahan Bantu Mengajar - Ilias, Mohd Faeez; Madzalan, Julia; Mohd Pisol, Mohd Izzuddin; Jamar, Annasaii; Abdullah, Murihah (Sains Humanika, 2022)
The use of teaching aids (TA) in the classroom is necessary to ensure that the teacher’s explanations in teaching and learning (T&L) process are easily comprehended by students. The TA materials used depend on the needs of the teacher in accordance with the T&L design that will be implemented. However, the use of TA is not an undemanding matter as it requires the teacher’s keenness in carrying out the plan that has been designed. Therefore, this study aims to analyse the obstacles that exist among Islamic Education Teachers (GPI) during the use of TA. Qualitative design was used to obtain interview data upon five GPIs and five GPI supervisors at the Smart School. The interview results were analysed using the NVivo 7.0 software by generating the theme of the study findings. Based on the analysis, there are eight obstacles listed by the GPIs on the use of teaching aids. All of these then form a pattern of study findings that perpetuates the two main obstacles for Islamic Education Teachers in the use of teaching aids, namely time and preparation. The results of this study are very meaningful to the Malaysian Ministry of Education (KPM), the State Education Office (JPN), and school administrators. The findings of this study show that the teachers need to be given time for the preparation to implement the planning of TA in the PdP process.